Tape casting of UV-curable aluminium nitride-based slurries. Issue 18 (15th December 2018) - Ożóg, P.; Kata, D.; Graule, T.
Abstract: Aluminium nitride (AlN) is one of the materials used for the preparation of substrates for electronic circuits. Such substrates can be prepared via tape casting method. Until now, only non-aqueous and aqueous tape casting was developed and studied for AlN. In this work, the development of UV-curable tape casting for AlN, including the use of photopolymerisable binder, is shown. Two different dispersing agents, BYK-W 9010 and glycerol trioleate, were used to stabilize and homogenize AlN dispersions. In order to modify the powder surface, a pre-treatment step was used, where the powder was first mixed with the dispersing agent in an azeotropic solvent mixture, followed by the evaporation of the solvents and the redispersing of the pre-conditioned powder into the reactive binder. The effective concentration of the dispersants, the impact of the solid loading on the viscosity and slurry behaviour, as well as the effect of the powder pre-conditioning, were studied by means of rheological measurements. Green tapes were optimised by evaluating the effect of the casting gap and the photo- and co-initiator concentrations. Finally, FTIR measurements were used to estimate the polymer conversion degree as a function of exposure time for the green tapes.